Egressos do curso de licenciatura plena em educação física na UFES (1995 - 2002) : aspectos da sua trajetória formativa e profissional - Martins, Maria Luiza Raphael Del Rio (2014)
This investigation is composed by a greater research that intended to follow the students whose major is Physical Education in the Physical Education and Sports Center (CEFD) at the Federal University (UFES), State of Espírito Santo, in the period from 1995 to 2010. A total of 395 students graduated between the end of the first semester in 1995 and the end of the second semester in 2010, composed the universe of this study stage. The instrument used was a questionnaire formed by open and closed questions that enabled to delineate a profile of the group analyzed, as well as outlining aspects of the formative and professional trajectory. The research located 80% of the graduated students‟ universe and 33,67% answered the questions corresponding to one third of the total. The work systematizes aspects of the formative and professional path of these former students through two themes: the knowledge dealt in the initial formation and carrier perspectives and Teachers‟ professionalism. In general, relating these subjects initial formation with their entry in the labor market, for most of the people, the initial formation assisted (94%), prepared (67%) to professionally act in the area, also influenced in the choice to act in the Physical Education area working at the moment (67%). The text stands out that the actuation field, significantly more occupied by these graduated students, is the formal education area in private, state, municipal and/or federal education networks. The researcher shares some concerns about the complex scenario that the issues regarding the Physical Education formation and the intervention are immersed, bringing data that reveal the academic and professional history of the graduated students.